Design And Transient Thermal Analysis Of Few Welding Using Conical Tool - Prakash, Vodnala Veda; Venugopal, Bachewal; Suresh, S.; Suresh, S. Suresh (International Journal of Psychosocial Rehabilitation, 2025)
Friction Stir Welding (FSW), invented by Wayne Thomas at TWI Ltd in 1991 overcomes many of the problems associated with traditional joining techniques. FSW is a solid-state process which produces welds of high quality in difficult-to-weld materials such as aluminium, and is fast becoming the process of choice for manufacturing lightweight transport structures such as boats, trains and aeroplanes. Aluminium alloys are lightweight materials relatively used in automotive industries. In FSW, the welding tool motion induces frictional heating and severe plastic deformation and metal joining process is done in solid state results, which results in defect free welds with good mechanical properties in aluminium alloy 5083.  A study was made of weldability of 4mm-thick Aluminium alloy 5083 plates using friction stir welding. The plan of experiments was prepared based on abilities of universal milling machine. The welding parameters in Friction Stir Welding (FSW) play a principle role in quality of the weld. The tool rotational speeds of 900r/min, 1120r/min, 1400r/min and 1800r/min, the welding speed of at 40mm/min were taken. The butt-joint types of aluminium plates were welded and then mechanical and thermal properties were to be analyzed. The microstructures of various regions were observed and analyzed by means of optical and scanning electron microscope. The tensile properties and micro-hardness were evaluated for the welded joint. The speeds are 900rpm, 1120 rpm, 1400rpm and 1800rpm. The temperatures taken for thermal analysis were also varying with the tool rotational speeds respectively. The effects of different tool pin profiles on the friction stir welding will also be considered for analysis. Different tool pin profiles are circular, tapered circular. As the joining process in friction stir welding is done below the melting point of base metal, it can be considered as the most significant development in metal joining world. It is essential to measure the amount of temperature distribution during friction stir welding as it had direct influence over the mechanical properties of the weld zone and heat affected zone. However, it is difficult to measure temperature in the weld zone due to the plastic deformation produced nonconsumable rotating tool. In this research proposal, development in the analysis of heat generation and temperature distribution are addressed.